‘Without ceasing to speak our language and without letting our culture die’: An interview with Cláudia Ferraz, from the Wayuri Network of Indigenous Communicators of Rio Negro/AM (Revista Internacional de Folkcomunicação, 2025)
During the COVID-19 pandemic, the popularization of podcasts was crucial for the protection and survival of population groups that have historically had their relevance and needs relegated to the background in news production, marginalized by conventional communication. In an interview with the International Journal of Folkcommunication, Cláudia Ferraz, from the Wanano people, tells how the Wayuri Network of Indigenous Communicators of Rio Negro carries out essential work to strengthen the region's indigenous cultures, recognized and awarded for its effectiveness during the global health crisis and which continues to reinvent itself to keep up with technological developments while preserving its roots and native languages.